Unveiling Cyberlaw and Cyberbullying: A Scholarly Overview - Hasmara, Shilla; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
In this research, data was collected and analyzed to provide insights into the field of cyberlaw and its relation to cyberbullying. The objective was to create a comprehensive overview of scholarly works in this domain. The data collection process involved using the Lens.org platform to search for articles related to "Cyberlaw OR Cyber Law AND cyberbullying." Subsequently, articles were filtered by document type, year published (from 2002 to 2012), and subject matter (Law). The collected data, comprising 1,631 articles, was analyzed to explore top institutions, publishers, fields of study, active countries/regions, authors, and more. The results provide a valuable resource for researchers, students, and journalists seeking information on cyberlaw and cyberbullying. The rich dataset can be leveraged for further insights and experimental development. This comprehensive analysis offers a deep understanding of the current state of cyberlaw research and its intersection with the pressing issue of cyberbullying. Highlight: Comprehensive Data: This research involved extensive data collection from Lens.org to create a vast dataset of articles related to cyberlaw, offering an invaluable resource for scholars. Scholarly Insights: The analysis provided a scholarly overview of cyberlaw research, identifying top institutions, publishers, and key areas of study in the field. Resource for Researchers: The resulting dataset serves as a valuable resource for researchers and students, enabling further exploration of the evolving landscape of cyberlaw. Keywords: Data Collection, Cyberlaw Research, Scholarly Analysis